2009
DOI: 10.1016/j.crvi.2008.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The dynamic changing of Ca2+ cellular localization in maize leaflets under drought stress

Abstract: Maize cultivar zhengdan958 was selected as materials. The sub-cellular distribution of soluble calcium at different phases was shown by the potassium-pyroantinonate-precipitation method and transmission electron microscopy. The results showed that the deposits of calcium antimonate as the indicator for Ca 2+ localization were mainly concentrated within the vacuoles and intercellular spaces without PEG treatment. Firstly, when the leaf was treated with PEG, the Ca 2+ level increased remarkably in the cytoplasm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 70 publications
(147 reference statements)
1
11
0
Order By: Relevance
“…This result showed that the increase of cytosolic Ca 2þ concentration induced by PEG was primarily due to extracellular Ca 2þ influx, and a little partially due to cytosolic Ca 2þ sources' release. This is in accordance with the results we have obtained in both guard cells and mesophyll cells through laser confocal and electronic microscopes technology [10,20].…”
Section: Discussionsupporting
confidence: 93%
“…This result showed that the increase of cytosolic Ca 2þ concentration induced by PEG was primarily due to extracellular Ca 2þ influx, and a little partially due to cytosolic Ca 2þ sources' release. This is in accordance with the results we have obtained in both guard cells and mesophyll cells through laser confocal and electronic microscopes technology [10,20].…”
Section: Discussionsupporting
confidence: 93%
“…EGTA, a calcium-chelating agent, is routinely used to establish the involvement of calcium ions in various physiological processes. [22][23][24][25][26][27][28][29][30][31][32][33][34][35] It forms stable, water-soluble complexes with calcium ions, thereby blocking their passage across plasma membrane into the cell. 24 Safadi et al 25 reported the presence of a calcium-dependent proteinase (CDP) activity in the roots of Arabidopsis, using in gel assays.…”
Section: Resultsmentioning
confidence: 99%
“…When Ca is applied to leaves, it enhances their ability to conserve water (Shao et al 2008 ) . In addition, Ma et al ( 2009 ) showed that Ca 2+ alters the degree of hydration of the plasma membrane and improves the cohesion of cell walls, which increases the viscosity of the protoplasm and the resistance of cells to dehydration. Berkowitz et al ( 2000 ) demonstrated that Ca 2+ inhibits the infl ux of K + to guard cells during water stress by affecting inward rectifying K + channels.…”
Section: Drought Stressmentioning
confidence: 98%